2010
DOI: 10.1128/jcm.01289-10
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium macginleyi Conjunctivitis in Canada

Abstract: This report describes for the first time Corynebacterium macginleyi as a cause of conjunctivitis in Canada, where menaquinone analysis was done as part of the strain characterization. This species is typically isolated from ocular surfaces of patients from Europe and Japan. The isolate was resistant to erythromycin and clindamycin. CASE REPORTA 54-year-old microbiologist was seen by an ophthalmologist in Winnipeg, Manitoba, Canada, for evaluation of bilateral conjunctivitis. She had no history of eye injury or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…was cultured at the highest rate. Ochrobactrum intermedium was observed in 23 of 33 eyes with Ochrobactrum spp, and this strain was not well identi ed by previous biochemical research methods, but is known to be identi ed by MALDI-TOF mass spectrometry, a commonly-used identi cation method [26]. In other words, in previous domestic studies [5][6][7], it was thought that it was di cult to identify this strain because bacteria were mainly identi ed using biochemical methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…was cultured at the highest rate. Ochrobactrum intermedium was observed in 23 of 33 eyes with Ochrobactrum spp, and this strain was not well identi ed by previous biochemical research methods, but is known to be identi ed by MALDI-TOF mass spectrometry, a commonly-used identi cation method [26]. In other words, in previous domestic studies [5][6][7], it was thought that it was di cult to identify this strain because bacteria were mainly identi ed using biochemical methods.…”
Section: Discussionmentioning
confidence: 99%
“…In ammation caused by this strain was uncommon, so it was only reported as a case in 2010, and it was reported that it mainly caused conjunctivitis, keratitis, and endophthalmitis. [24][25][26][27][28] It is generally known that it does not cultivate well in healthy conjunctiva. In this study, the single strain was cultured the second most after S. epidermidis.…”
Section: Discussionmentioning
confidence: 99%
“…was cultured at the highest rate. Ochrobactrum intermedium was observed in 23 of 33 eyes with Ochrobactrum spp, and this strain was not well identified by previous biochemical research methods, but is known to be identified by MALDI-TOF mass spectrometry, a commonly-used identification method [ 23 ]. In other words, in previous domestic studies [ 5 – 7 ], it was thought that it was difficult to identify this strain because bacteria were mainly identified using biochemical methods.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that Corynebacterium macginleyi is the dominant species among nondiphtherial corynebacteria isolated from the normal conjunctival sac and from cases of bacterial conjunctivitis (3,5,(8)(9)(10)(11). However, the literature contains only a few reports of corneal infection caused by C. macginleyi (6,11,12).…”
mentioning
confidence: 99%
“…These bacteria occasionally cause conjunctivitis in aged patients, suturerelated corneal infection, and on rare occasions, keratitis in compromised ocular surfaces (5)(6)(7)(8)(9)(10)(11). However, there is little information about which species are related to keratitis, because species identification is not performed routinely in most hospitals or laboratories.…”
mentioning
confidence: 99%